AWARENESS OF NON COMMUNICABLE DISEASES AND THEIR RISK FACTORS AMONG RURAL SCHOOL CHILDREN - Shivalli, Siddharudha; Gupta, Manoj Kumar; Mohaptra, Archisman; Srivastava, Ratan Kumar (Indian Journal of Community Health, 2012)
Introduction: Behavioral interventions for Non Communicable Diseases (NCD) abeyance would profit the most, if initiated at an early age. Major risk factors of NCDs are changing life style and behavior pattern which are largely due to practices adopted in younger age. Students' awareness about NCDs and their risk factors is an important part of population based prevention strategy. Objective: To assess the awareness of NCDs and their risk factors among rural intermediate school children. Methodology: A School based cross sectional study was conducted in Chiraigaon Community Development Block of Varanasi from July - Aug 2010. Intermediate school children from eight inter-colleges of Chiraigaon development block were the study subjects. Pretested questionnaire was used in the study and frequency and proportions were used to analyze the data. Results: Less than one third of the children were aware about Diabetes and Hypertension (27% and 31% respectively). Only 18% knew about Body Mass Index (BMI) as an indicator of obesity. In general awareness of NCDs was more in boys than girl. Conclusion: Over all awareness of NCDs and their risk factors among students was not satisfactory. There is a need and scope for health education activity regarding NCDs and their risk factors to promote healthy life style among these school children.